SUBORDINASI PERAN SOSIAL PEREMPUAN (ANALISIS TERHADAP CERPEN â€œLAILAâ€ KARYA PUTU WIJAYA) - Ida Novianti (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2015)
Todays, violence and subordination experienced by women in the domestic sphere into the events that are familiar ineveryday life. The Government has been providing products Law Number 23 Year 2004 on the Elimination of Violence in Household.However, this law has not effectively curb the violence that occurs in women. This social reality portrayed by Putu Wijaya in a short story toopen the eyes of the community that the events portrayed in the short story